The Arabic influence on Northern Berber - Kossmann, Maarten G. (Leiden ; Boston : Brill, 2013)
"The Arabic Influence on Northern Berber provides an overview of the effects of language contact on a wide array of Berber languages spoken in the Maghrib. These languages have undergone important changes in their lexicon, phonology, morphology, and syntax as a result of over a thousand years of Arabic influence. The social situation of Berber-Arabic language contact is similar all over the region: Berber speakers introducing Arabic features into their language, with only little language shift going on. Moreover, the typological profile of the different Berber varieties is relatively homogenous. The comparison of contact-induced change in Berber therefore adds up to a study in typological variation of contact influence under very similar linguistic and social conditions."--Provided by publisher
6.2.1 Non-Integrated Borrowings: General Features6.2.2 Paradigmatic Gender Relationship in Non-Integrated Borrowings; 6.3 Integrated Borrowings with Retention of the Arabic Article; 6.4 Non-integrated Borrowings Lacking the Arabic Article; 6.5 The Distribution of Integrated and Non-Integrated Borrowings over the Lexicon; 6.6 Comparing Berber Morphology and Non-Integrated Morphology; Chapter Seven Verbal Morphology; 7.1 General Morphological Facts; 7.2 Arabic Derived Forms in Berber; 7.3 The Insertion of Arabic Verb Shapes into Berber Morphology.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Berber languages -- Foreign elements -- Arabic; Arabic language -- Influence on Berber; Languages in contact -- Africa, North; Langues en contact -- Afrique du Nord; Arabe (Langue) -- Influence sur le berbère.; FOREIGN LANGUAGE STUDY -- African Languages; Berber languages -- Foreign elements -- Arabic; Arabic language -- Influence on Berber; Languages in contact; North Africa; Berbersprachen; Sprachkontakt; Arabisch; Entlehnung; Nordafrika; Electronic book